CORRECTION OF NUTRITIONAL STATUS IN COMPLEX THERAPY FOR CHILDREN SUFFERING FROM DYSTROPHIC FORMS OF INNATE EPIDERMOLYSIS BULLOSA - S. G. Makarova; L. S. Namazova-Baranova; N. N. Murashkin; R. V. Epishev; T. R. Chumbadze; M. I. Petrovskaya; I. L. Mityushin (Педиатрическая фармакология, 2017)
Children  suffering  from  dystrophic  forms  of  innate  epidermolysis  bullosa  (IEB),  have  malnutrition  of  multifactorial  genesis.  And, despite the experience of working with this complex group of patients, many practical issues of optimal nutrition organization at IEB remain  unsolved.  The review presents  modern  approaches  to the assessment  of nutritional status  with children,  including those developed for the assessment of eating disorders with children having IEB; the formulas for calculating the nutrient requirement are presented. The analysis of the scientific data on the pathogenesis and characteristics of disturbances in nutritional status with children having IEB is done. It is noted that the complexity of nutritional support of this severe category of patients is due to a mismatch between the increased need for nutrients and limited assimilation of food, which requires a special diet with increased energy and protein value without increasing the amount of food intake. Reasonability of the organization of feeding children having IEB with specialized products for enteral nutrition and nutritional support is analyzed.